HUBUNGAN TINGKAT KECUKUPAN ENERGI, MAGNESIUM, KALSIUM DAN BESI, AKTIVITAS FISIK, PRESENTASE LEMAK TUBUH DENGAN SIKLUS MENSTRUASI REMAJA PUTRI SMA NEGERI 4 KOTA PEKALONGAN - Dinda Sofia Triany; Laksmi Widajanti; Suyatno Suyatno (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Menstrual cycle disorder is a problem that has found quite often by adolescents. The objective of the research was to determine the relationship of energy, magnesium, calcium, and iron adequacy, physical activity, body fat percentage with menstrual cycle of adolescents in Senior High School 4 Pekalongan. This research used a cross-sectional approach. The population of this research counted to 343 girls 16-18 years and the sample in this research were 73 female samples with proportional random sampling technique that was taken by representatives adolescents of each class who were willing to become respondents. Data analysis used Rank Spearman and Chi-Square Test. The result showed that some of adolescents had abnormal menstrual cycles (63.3%), the levels of energy severe deficits (47.9%), sufficient levels of magnesium (54.8%), the level of calcium adequacy was lacking (76, 7%), the level of iron adequacy was lacking (79.5%), mild physical activity (78.1%), percentage of body fat was normal (64.4%). There was relationship between menstrual cycle length and energy adequacy level (p=,043, ρ=-0,238), magnesium adequacy level (p=0,049, ρ=-0,231), calcium adequacy level (p=0,031, ρ=-0,252), iron adequacy level (p=0,007 ρ=-0,311), body fat percentage (p=0,040, ρ=-0,242) which means the lower level of sufficiency of energy, calcium, magnesium and iron, the menstrual cycle becomes longer than normal (oligomenorea), and the increasing percentage of body fat the menstrual cycle becomes shorter than normal (polimenore). There was no relationship between menstrual cycle length and physical activity (p=0,338, ρ=-0,114). It is advisable for adolescents to consume high-energy foods such as beef and eggs. High-calcium foods such as cheese, milk, shrimp and fish and high-iron foods such as chicken's liver, eggs and nuts so,it could maintain nutritional intake can balance the percentage of body fat to remain normal.